2014
DOI: 10.1007/s11746-014-2425-2
|View full text |Cite
|
Sign up to set email alerts
|

Content and Fatty Acid Composition of Neutral Acylglycerols in Euonymus Fruits

Abstract: The content and fatty acid (FA) composition of FA neutral acylglycerols (NAG), a mixture of 1,2,3‐triacyl‐sn‐glycerols (TAG) and 3‐acetyl‐1,2‐diacyl‐sn‐glycerols (acDAG), were determined in the seeds and arils of fruits of 14 Euonymus L. species. On the average, the seeds exceeded the arils in the absolute and relative dry matter content 2.9‐ and 1.9‐fold, respectively, and separate plant species greatly differed in NAG composition. The proportions of TAG in the NAG of seeds and arils were 4–5 and ~98 %, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…Euonymus europaeus L., E. bungeanus MAXIM., E. hamiltonianus WALL., E. phellomanus LOES., E. semiexcertus KOEHNE, E. sieboldianus BLUME, E. macropterus RUPR., E. maximowiczianus (PROKH.) VOROSCH., E. latifolius MILL., E. sachalinensis MAXIM., E. pauciflorus MAXIM., E. alatus, E. verrucosus, and E. sacrosanctus KOIDZ., belonging to several sections of both subgenera of this genus [11] [12]. We have found that the separate taxonomic units of this genus differ from each other at the concentration of major FAs.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Euonymus europaeus L., E. bungeanus MAXIM., E. hamiltonianus WALL., E. phellomanus LOES., E. semiexcertus KOEHNE, E. sieboldianus BLUME, E. macropterus RUPR., E. maximowiczianus (PROKH.) VOROSCH., E. latifolius MILL., E. sachalinensis MAXIM., E. pauciflorus MAXIM., E. alatus, E. verrucosus, and E. sacrosanctus KOIDZ., belonging to several sections of both subgenera of this genus [11] [12]. We have found that the separate taxonomic units of this genus differ from each other at the concentration of major FAs.…”
Section: Introductionmentioning
confidence: 78%
“…However, these authors have not taken into account that Euonymus seeds along with AcDAGs containing some quantity of TAGs were also well hexane extractable. Despite the identification of AcDAGs peaks was based on APCI‐MS data ( M + and M + H + ) , it is possible that quantitative data were distorted by TAGs admixture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations